Integrating motion capture in a virtual reality intervention planning platform to study radiation protection measures for the ATLAS inner detector decommissioning. (12th March 2021) - Cryer, A.; Kapellmann-Zafra, G.; Marin-Reyes, H.; Lohwasser, K.; Steel, A.; Veale, K.; Jaekel, M.
Abstract: An intervention planning and evaluation platform has been developed to enable dose estimation and personnel training for the ATLAS inner detector decommissioning. The present paper describes the integration of motion capture into the system, including the dose estimation results for the recorded decommissioning steps.